Why Africa Needs The COP Project Badly - Lane, Jan-Erik (Advances in Social Sciences Research Journal, 2018)
To meet the demands for rising living standards in this century, Afican countries need to upgrade its energy supply. They can only do it with massive support from the COP project, which would reduce the global warming risk, globally. Solar power parks like Quarzazate is the future for the African continent.